Mary Ann Bickerdyke papers - Bickerdyke, Mary Ann, 1817-1901.
Correspondence, draft memoirs, lists, biographical material, printed matter, and other papers relating to Bickerdyke's work as a Civil War nurse and agent for the United States Sanitary Commission, her activities on behalf of Civil War veterans in the years following the war, and family affairs. Includes papers relating to James H. Cook and the Woman's Relief Corps (U.S.). Family correspondents include Bickerdyke's sons, Hiram Bickerdyke and James Bickerdyke, and members of the Ball and Bickerdyke families. Correspondents include Lucien Baker, Richard Whiting Blue, Dorothea Lynde Dix, Mary Ashton Rice Livermore, Walden Perkins, Theodore Roosevelt, and Lucy Stone.
Nurse, agent for the U.S. Sanitary Commission, and pension attorney. Born Mary Ann Ball; known as "Mother" Bickerdyke to Union soldiers.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baker, Lucien -- Correspondence; Bickerdyke, Hiram -- Correspondence; Bickerdyke, James -- Correspondence; Blue, Richard Whiting -- Correspondence; Cook, James H; Dix, Dorothea Lynde, -- 1802-1887 -- Correspondence; Livermore, Mary Ashton Rice, -- 1820-1905 -- Correspondence; Perkins, Walden -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Stone, Lucy, -- 1818-1893 -- Correspondence; Ball family; Ball family -- Correspondence; Bickerdyke family; Bickerdyke family -- Correspondence; United States Sanitary Commission; Woman's Relief Corps (U.S.); Military pensions -- United States -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Medical care; United States -- History -- Civil War, 1861-1865 -- Veterans; United States -- History -- Civil War, 1861-1865 -- War work; Lawyers; Nurses